The salineros mitmas of Tarma, Chinchaycocha and Pasco, 20th century BC. - XX AD - Espinoza Soriano, Waldemar (1984)
It has long been known of the existence of salt springs located both in the territory of the Chinchaycochas and Tarmas as well as in the Yaros and Huancas. It is known, with complete certainty, that the Chinchaycochas, Tarmas and Huancas obtained sodium chloride by boiling and evaporating these waters, a method that forced them to consume a great deal of fuel (taquia and ichu) and also a great demand for clay containers, primarily pots.